How to face growing competition - Wolfgang Reisener (Intereconomics, 1967)
Hamburg's port, as a transshipment terminal and centre of trade, has more than national importance. Exporters and importers, shipowners and seafarers all over the globe know Hamburg as an international port of world rank. The exchange of goods across the seas lifts our port into the position of a catalyst drawing together the continents through a network of marine transport connections that grows progressively more elaborate. Government authorities and business people have joined together in Hamburg to undertake a vast task of reconstruction, when Hamburg's port was to be restored, after the last war, to its world importance. Hamburg's policies on port questions are devoted to the supreme effort of keeping the port abreast of the changing demands of future trade and transport. The present report is based on a highly authoritative study of the position and the development prospects of the port of Hamburg, that has been compiled by the Hamburg Department for Economic Affairs and Transport and was recently published
Keywords: 330; The Port of Hamburg